Development of an acrylamide-free palm sugar-like flavouring using maillard reaction - Tan, Phui Yee (2013)
Palm sugar-like flavouring (PSLF) can be produced by heating a mixture of amino acids, sugar and sodium phosphate buffer (NaHPO4) via the Maillard reaction. The main problem of the resulting PSLF was the saltiness and presence of a significant amount of acrylamide. Thus, the main objective of this research was to minimise the saltiness and acrylamide without adversely affecting the PSLF aroma quality. This study consisted of the following three main stages: the first stage involved preliminary and response surface methodology (RSM) experiments; the second stage involved the replacement of NaHPO4 with potassium phosphate (KHPO4) buffer; and finally, a sensory evaluation of the optimised PSLF in food was carried out. The modified PSLF buffer system significantly (p<0.05) reduced the sodium content from 728.19 ± 26.68 to 45.90 ± 0.55 mg/g fresh weight (FW) in comparison with the original PSLF. PSLF without CaCl2 was found to contain higher acrylamide and lower flavour contents compared to the other concentration levels. Based on preliminary results, a two-factor, three-level face-centred central composite design was employed to optimise the CaCl2 (20-80 mg/L) and asparagine concentrations (0-25.50 mM). Both CaCl2 and asparagine exhibited a positive linear interaction (p<0.05) effect on acrylamide. Acrylamide was lowest in the presence of 20 mg/L CaCl2 and 0 mM asparagine. Both factors imparted a quadratic effect on all of the flavour compounds, namely 2-ethyl-3, 5-dimethylpyrazine (EDMP), 2, 3-diethyl-5- methylpyrazine (DEMP), 5H-5-methyl-6, 7-dihydroxycyclopentapyrazine and 4H-2,5-dimethyl-3(2H)-furanone (furaneol). Without the use of asparagine did not negatively affect the overall PSLF flavour quality. Thus, the optimised concentrations were 20 mg/L CaCl2 and 0 mM asparagine. By using the optimised formula, the Na2HPO4 in PSLF was replaced with various concentrations of K2HPO4 to further reduce the sodium content. A 0.200 M concentration of K2HPO4 most effectively reduced the sodium content while providing a good flavour profile in the PSLF. This final optimised formula was subjected to hedonic preference testing in comparison to the commercial palm sugars in sago-based palm sugar. PSLF was less preferred and received lower acceptability in contrast to the commercial products, which might be explained by consumer familiarity with the commercial products, causing the testers to not accept the novel taste. Additionally, based on a few comments on the perception of sourness in PSLF, the taste of the product could be improved by further amending the PSLF formula in the future.